Empowering the Anambas Islands Community Through Waste Education and the Potential of Utilizing Mangrove Waste into Bioplastics - Hidayati, Jelita Rahma; Febrianto, Try; Susanti, Susanti; Sinaga, Ronald Raditya Kesatria; Laia, Dominikus Yoeli Wilson; Alifiya, Rosyita; Handoko, Eddy; Murwanto, Murwanto; Anggraini, Rika; Nugraha, Aditya Hikmat; Arifatin, Ilil; Aditianda, Said Rully; Anjani, Poppy Yulia; Aulia, Hilyatul; Achmadiah, Soneta (Jurnal IPTEK Bagi Masyarakat, 2026)
Waste, particularly plastic, poses a serious threat to coastal ecosystems in the Anambas Islands, Riau Islands Province. This community service program collaborated with LKKPN Pekabaru and Yayasan Jaga Mangkai aimed to enhance environmental literacy, raise awareness on waste management, and introduce the potential of mangrove waste (Bruguiera gymnorhiza) as raw material for environmentally friendly bioplastic. The methods included educational sessions, interactive discussions, coastal clean-up activities, and evaluation using pre-test and post-test questionnaires. The results revealed that from 407.1 kg, 69% of the collected waste consisted of non-plastic categories. Laboratory tests on mangrove waste indicated the presence of active compounds with potential for bioplastic production. Questionnaire evaluation showed a significant improvement in community understanding, with average scores exceeding 50% in aspects of waste knowledge, bioplastic innovation, and attitudes toward environmental management. In conclusion, the program effectively increased ecological awareness and highlighted the potential for local innovation based on coastal resources. Nevertheless, follow-up programs are necessary to ensure that improved knowledge is transformed into sustainable daily practices in waste management.